Increase of Incidence and Mortality of Ovarian Cancer during 2003–2012 in Jiangsu Province, China - Teng, Zhimei; Han, Renqiang; Huang, Xingyu; Zhou, Jinyi; Yang, Jie; Luo, Pengfei; Wu, Ming (Frontiers in Public Health, 2016)
Purpose The objective of this study is to investigate and analyze the epidemiologic characteristics and time trends of ovarian cancer incidence and mortality in Jiangsu Province of China during 2003–2012. Method Data were collected from eligible cancer registries in Jiangsu Province. Crude rates, age-specific rates, truncated age-standardized rate, and proportions of ovarian cancer were calculated. The Segi’s World Population was used to calculate age-standardized rates for world (ASW). Poisson distribution was used to analyze the differences between urban and rural areas. Joinpoint regression was performed to estimate the annual percent change (APC) of ovarian cancer incidence/mortality. Results A total number of 4,401 new cases and 1,918 deaths were identified during period 2003–2012. The incidence and mortality ASW was 3.64/100,000 and 1.52/100,000, respectively. ASW of incidence was 4.48/100,000 in urban areas, while 3.04/100,000 in rural areas. The mortality of ASW was slight higher in urban areas than in rural areas. Age-specific incidence showed a peak at the age group of 60–64 years, whereas mortality peaked at age group of 65–69 years. A significant increase of incidence was observed from 2003 to 2006, with an APC of 34.0% (95% CI: 9.7, 63.7), the increasing rate declined since 2006 (APC = 3.3%, 95% CI: −3.5, 10.5). The mortality showed a gentle upward trend as compared with incidence, with an APC of 9.9% (95% CI: 7.7, 12.2) per year, continuously from 2003 to 2012. It is apparent that both incidence and mortality presented a rising trend in all areas, but urban were higher than that in rural areas. Conclusion Ovarian cancer is a highly lethal disease which is becoming a significant public health problem in Chinese women. It is vital to improve the understanding of current status of ovarian cancer. Moreover, prevention and control policies should be formulated to reduce the disease burden of ovarian cancer in China.